Journalismin kriisistä amerikkalaisittain - Väliverronen, Jari (Media & viestintä, 2023)
Barbie Zelizer, Pablo J. Boczkowski ja Chris W. Anderson. 2021. The Journalism Manifesto. Cambridge: Polity, 123 s.